Analisa Kriminologis Kejahatan Pencurian Berdasarkan Teori Differential Association - Sari, Widia; Farida, Hana (Fakultas Hukum Universitas PGRI Kanjuruhan Malang, 2021)
Theft is one of the most basic topics in criminal justice and sociology. There are researchers from various fields trying to find significant reasons for this problem; whether it is sociological, physical or psychological. To find out what are the factors behind the occurrence of the crime of theft based on the theory of differential association and to be a learning material in order to minimize the crime. The method used in writing this journal article is by using data and data sources and drawing conclusions. Stated that delinquent behavior was learned and adhered to by criminal parents or criminal groups. This departs from the concept of differential association theory, and there are several studies examining this relationship showing how peer delinquency is related to the transition between theft and problematic behavior that occurs together. In addition to the influence of peer groups and deviant parents, the researchers also found that a bad environment, fragile personality, and poverty play an important role in the theft committed by minors. such as family (socialization) and school (education).